Pamięć i tożsamość w nauczaniu historii (komunikat) - Pańko, Grażyna (Uniwersytet Wrocławski Wydział Nauk Historycznych i Pedagogicznych Instytut Historyczny, 2021)
The author draws attention to the fact that the goal of the teacher’s work is to make students understand past and present events and become convinced that the past helps understand the world in which they live and also to avoid making mistakes in the future. The definition of content and skills resources is included in the core curriculum, but it is the teacher who decides when and how to introduce them to the teaching of a specific group of young people.